A finite-buffer queue with a single vacation policy: An analytical study with evolutionary positioning - Woźniak, Marcin; Kempa, Wojciech M.; Gabryel, Marcin; Nowicki, Robert K. (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, application of an evolutionary strategy to positioning a GI/M/1/N-type finite-buffer queueing system with exhaustive service and a single vacation policy is presented. The examined object is modeled by a conditional joint transform of the first busy period, the first idle time and the number of packets completely served during the first busy period. A mathematical model is defined recursively by means of input distributions. In the paper, an analytical study and numerical experiments are presented. A cost optimization problem is solved using an evolutionary strategy for a class of queueing systems described by exponential and Erlang distributions.
Keywords: finite-buffer queue; evolutionary strategy; object positioning; queueing system; busy period; idle time; single vacation